Institutional Evolution of Subdistricts in Indonesia: Transformation of the Subdistrict Head’s Role from the Colonial Era to Contemporary Decentralization - Moh Arif Mulyawan R; Arif Nugroho (Jurnal Multidisiplin Sahombu, 2025)
The decentralization reform in Indonesia has transformed the institutional framework of sub districts (kecamatan) and shifted the role of the sub district head (Camat) from an administrative bureaucrat to an adaptive participatory development agent. This study employs a historical institutional approach and path dependency analysis to explore the evolution of sub district institutions from the colonial era to contemporary decentralization. The findings reveal significant disparities in institutional capacity among sub districts, influenced by the legacy of colonial bureaucracy and resource inequalities, which result in governance asymmetry and the risk of a decentralization trap. High capacity sub districts are able to optimize resources, social capital, and leadership for service innovation and community participation, whereas low capacity sub districts face stagnation. This study emphasizes the need for a governance model that integrates historical, structural, and socio political dimensions within a multi level governance framework, as well as a transformation of accountability toward performance based accountability. Strategic recommendations include strengthening performance based funding, human resource and leadership development, enhancing social capital, and transparent evaluation mechanisms to improve the quality of sub district governance in Indonesia.